Denticulatains A and B: unique stilbene–diterpene heterodimers from Macaranga denticulata1. Issue 18 (5th March 2015) - Yang, Da-Song; Li, Zi-Lei; Wang, Xue; Yan, Hui; Yang, Yong-Ping; Luo, Huai-Rong; Liu, Ke-Chun; Xiao, Wei-Lie; Li, Xiao-Li
<x xml:space="preserve">Abstract</x> Two novel heterodimers were isolated from the fronds of Macaranga denticulata. They possess an unprecedented stilbene–diterpene-type skeleton, which represents a unique class of prenylated stilbene.